Agricultural labour productivity growth and food insecurity transitions among maize farming households in rural Nigeria (2022)
Agriculture in rural Nigeria is labour-intensive. Thus, the much-desired transition from food insecurity to food security by households requires growth in labour productivity. Labour productivity growth and its effect among other factors on food security transitions of maize farming households in rural Nigeria were assessed. Food insecurity indices were constructed using the second and third waves of data from the General Household Survey- Panel (2012 and 2015), and a probabilistic model was specified. The analytical tools used were descriptive statistics, Partial factor (labour) productivity, Foster- Greer-Thorbecke Model, Markov chain model, Tobit, and Multinomial Logit Regression Models. Labour productivity increased between the two periods although labour productivity growth was very low. Labour productivity growth negatively and significantly affected the transition into food security and being chronically food insecure. Thus, a boost for labour productivity growth should be targeted as a safety net, especially for the food insecure and households vulnerable to food insecurity.